Gerwani Mazhab Politik Islam Era Soekarno - Deden Rahmanudin (Jurnal Kewarganegaraan, 2022)
AbstrakGerakan Wanita Indonesia (Gerwani) menjadi perbincangan menarik dalam sejarah Gerakan 1 Oktober (Gestok) atau yang diberi nama Gerakan 30 September oleh PKI (G30 S/PKI) oleh Pemerintah Orde Baru. Lahirnya Gerwani yang menjadi simbol perlawanan dan perjuangan wanita di Indonesia pada waktu itu bukan hal asing dalam perspektif Islam dalam memandang kesetaraan dan optimalisasi peranan wanita. Islam yang memiliki mazhab politik rahmatan lil alamiin, tentu memandang penting hal ini. Namun keberadaan Gerwani menjadi suatu gerakan yang dianggap berbahaya oleh Negara di era Soeharto, membuat organisasi ini tidak mampu berkembang dengan baik. Akan tetapi corak pergerakan yang mengatasnamakan perjuangan gender ini masih digunakan sebagai paradigma berfikir dari setiap pergerakan wanita di Indonesia. Banyak tokoh wanita termasuk muslimah yang lahir dari gerakan perjuangan kesetaraan ini. Yang perlu dikaji lebih mendalam adalah ideologi yang dianut oleh Gerwani dalam konteks bernegara dan beragama, atau oleh founding father Indonesia dirangkum dalam kebhinekaan cara pandang bangsa yaitu Pancasila. Maka, perlu didapatkan sebuah gagasan penting dalam mengetahui Gerwani ini dalam kajian Islam.Kata Kunci: Gerwani, Politik, Islam, FeminismeÂ AbstractThe Indonesian Women's Movement (Gerwani) became an interesting conversation in the history of the October 1st Movement (Gestok) or what was named the September 30th Movement by the PKI (G30 S / PKI) by the New Order Government. The birth of Gerwani, which became a symbol of women's resistance and struggle in Indonesia at that time, was not unfamiliar with the Islamic perspective in looking at equality and optimizing the role of women. Islam, which has a political school of rahmatan lil alamiin, certainly sees this as important. However, the existence of Gerwani became a movement that was considered dangerous by the State in the Soeharto era, making this organization unable to develop properly. However, the pattern of movement in the name of gender struggle is still used as a thinking paradigm of every women's movement in Indonesia. Many female figures including Muslim women were born from this equality struggle movement. What needs to be studied more deeply is the ideology adopted by Gerwani in the context of statehood and religion, or by the Indonesian founding father summarized in the diversity of the nation's perspective, namely Pancasila. Thus, it is necessary to get an important idea in knowing this Gerwani in Islamic studies. Keywords: Gerwani, Politics, Islam, Feminism